Local Wisdom of Banana Farmers in Building Sociocultural Empowerment - Wibowo, Agung; Lestari, Eny; Rahayu, Paramita (KnE Social Sciences, 2024)
The local wisdom of banana farmers in building sociocultural empowerment is a response to the challenges of globalization and climate change. Integrating tradition with modernization will achieve sustainability, a strong local identity, and community welfare. The revitalization of local wisdom in building socio-cultural empowerment is an important step in preserving traditional cultural heritage, strengthening local identity, and improving the welfare of agrarian communities. This article discusses the mechanism for the revitalization of the local wisdom of banana farmers in building sociocultural empowerment. A qualitative research method is used with a phenomenological approach. The research was conducted in the banana development center in Karanganyar Regency, Central Java. The research results show that the revitalization of the local wisdom of banana farmers in Karanganyar Regency in building sociocultural empowerment is implemented through a mechanism of, (1) education and training of the young generation; (2) development of communities and networking; (3) empowerment of farmers. By understanding how the local wisdom of farmers integrates tradition with modern innovations, the community can build strong sociocultural empowerment; withstand climate change; maintain sustainability of the farming culture; and improve the life quality of the community. Keywords: local wisdom, banana farmers, sociocultural empowerment